Pelatihan Kader Posyandu Dalam Perancangan Media Promosi Kesehatan Berbasis Digital di Kelurahan Jebres - Muhlizardy, Muhlizardy; Annisa Permatasari, Anggie; Asani, Fitrianti; Nur Istiqomah, Nadya (Al-Khidmah Jurnal Pengabdian Masyarakat, 2024)
The obstacles faced by the senior caders at RW 09 Jebres's current welfare are his ability to provide support to the community. Awareness of the cadres is still low. So the current knowledge, especially the problems of the elderly, is still not updated while the development of science continues to advance, thus making the service of cadres ineffective in the implementation of posyandu activities. Kader Posyandu should create a digital health promotion model like social media. Kader should combine social media with health communication and health promotion plans. There are many interesting online applications for editing content for health promotion, but cadres need to develop their ability to make full use of them. The method used in this digital-based health promotion media planning training is by dividing it into three stages, namely the preparatory stage, the implementation stage, and the post-implementation stage of evaluation and reporting. The event is a community service program held at RW 09 Kelurahan Jebres in July 2024. The result of these training activities is the increased knowledge of senior cadres to design health promotion media (66.7%), while the skills of most cadres are still under-skilled. In the future, he will be able to continue training senior cadres directly on the topic of senior health combined with skills to increase senior productivity